An O-Specific Polysaccharide/Tetanus Toxoid Conjugate Vaccine Induces Protection in Guinea Pigs against Virulent Challenge with Coxiella burnetii - Stephen R. Graves; Aminul Islam; Lawrence D. Webb; Ian Marsh; Karren Plain; Mark Westman; Xavier A. Conlan; Rodney Carbis; Rudolf Toman; John Stenos (Vaccines, 2022)
Q fever is caused by the bacterium Coxiella burnetii and is spread to humans from infected animals especially goats, sheep and cattle, predominantly when giving birth. There is an effective human vaccine (Q-VAX) against Q fever, and although Q fever is a worldwide problem, the vaccine is only used in Australia due to difficulties associated with its use and the risk of adverse reactions. The desire to protect humans, particularly farmers and abattoir workers, from Q fever prompted the development of a new safe and effective human vaccine without all the difficulties associated with the current vaccine. Candidate vaccines were prepared using purified O-specific polysaccharide (OSP) extracted from the lipopolysaccharide of virulent (phase 1) C. burnetii, strain Nine Mile, which was then conjugated to a tetanus toxoid (TT) carrier protein. Two vaccines were prepared using OSP from C. burnetii grown in embryonated eggs (vaccine A) and axenic media (vaccine B). Vaccines with or without alum adjuvant were used to vaccinate guinea pigs, which were later challenged by intranasal inoculation with virulent C. burnetii. Both vaccines protected guinea pigs from fever and loss of weight post challenge. Post-mortem samples of the spleen, liver and kidney of vaccinated guinea pigs contained substantially less C. burnetii DNA as measured by PCR than those of the unvaccinated control animals. This study demonstrated that a C. burnetii OSP-TT conjugate vaccine is capable of inducing protection against virulent C. burnetii in guinea pigs. Additionally, OSP derived from C. burnetii grown in axenic media compared to OSP from embryonated eggs is equivalent in terms of providing a protective immune response.